Creative Adaptability: Conceptual Framework, Measurement, and Outcomes in Times of Crisis - Orkibi, Hod (Frontiers in Psychology, 2021)
This article presents the framework and explores the measurement, correlates, and outcomes of creative adaptability (CA), proposed here as the cognitive-behavioral-emotional ability to respond creatively and adaptively to stressful situations. Data collection was in April 2020, during the peak of the outbreak of the Coronavirus pandemic (COVID-19) in Israel. In Study 1, a sample of 310 adults completed the newly-developed CA scale, as well as spontaneity, openness to experience, creative self-efficacy, and well-being measurements. The results of exploratory and confirmatory factor analyses corroborated the 9-item CA scale’s theorized underlying construct. The scale’s validity and reliability were also supported. Exploratory analyses suggested that the association between CA and well-being was mediated by creative self-efficacy and that CA may buffer the impact of individuals’ concern about Coronavirus on their well-being. In Study 2, short-term longitudinal data based on a sample of 71 students suggested that CA may predict lower psychological stress over time. Support for the CA scale’s internal consistency reliability was obtained and its test-retest reliability was established. Overall, the results shed light on this new construct as a potential protective factor. Implications for theory, research and practice are discussed.